Smoking Ban on Public Transport: How do we protect and advocate for consumers? - Sulistianingsih, Dewi; Adhi, Yuli Prasetyo; Syakila, Nabila Putri; Mohd Yusoff, Rahmawati (Indonesian Journal of Advocacy and Legal Services, 2025)
Public transportation is very important for the mobility of Indonesian society and is used by millions of people every day, there is still a big problem related to smoking. Many regulations, implementation and law enforcement are still difficult. This study uses a normative legal research method with a legislative approach, a conceptual approach, and a comparative approach. Data collection is carried out through tracing primary, secondary and tensier legal materials and literature studies. In addition, this study develops a model of harmonization of laws and regulations for law enforcement of smoking bans on public transportation through an integrated regulatory framework approach to consumer protection, health and transportation regulations. It aims to identify weaknesses in the regulatory and law enforcement system, and to formulate more effective strategies to protect the rights of public transportation consumers to a smoke-free environment, so that it can provide more optimal protection for the health and safety of public transportation users in Indonesia.